Peningkatan Pengetahuan Peran Fleksibilitas Dan Keseimbangan Dalam Kehidupan Sehari-hari Pada Posyandu Lansia Arso - Fachrun Nisa Sofiyah Khasanah; Citra Kumala Dewi; Muhammad Teguh Prasetyo; Itsna Rosyada (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
The increasing number of older adults has led to a rise in health-related problems, particularly those associated with decreased flexibility and balance, which may increase the risk of falls and reduce independence in daily activities. This community service program aimed to improve the knowledge of older adults regarding the role of flexibility and balance in daily. The implementation methods included health education, demonstrations of stretching and balance exercises, and guided independent practice. Evaluation was conducted using pretest and posttest to measure participants’ knowledge levels. The results showed a significant improvement in knowledge, where in the pretest the majority of participants were in the low category and very low category. After the intervention, there was a substantial increase in the high category and very high category. In addition, the low category decreased to 4.62%, and the very low category dropped to 0%. These findings indicate that the educational intervention was effective in improving the understanding of older adults. This program contributes to enhancing awareness and the ability of older adults to maintain their health through flexibility and balance exercises in order to sustain independence in daily living.